Incidence of armoured scale insects on persimmons - Tomkins, A.R; Wilson, D.J.; Thomson, C.; Allison, P. (New Zealand Plant Protection, 2000)
The incidence of armoured scale insects infesting persimmons (Diospyros kaki) grown in five districts (Whangarei (Northland) Pukekohe (South Auckland) Morrinsville (Waikato) Maketu (Bay of Plenty) and Gisborne (Poverty Bay)) was investigated over three growing seasons (1995/96 1996/97 and 1997/98) Three species of armoured scale insects were found on persimmon fruit greedy scale (Hemiberlesia rapax) latania scale (H lataniae) and oleander scale (Aspidiotus nerii) The species composition differed between districts with latania scale the most common species recorded overall Fruit were infested by the first and second generations of all three species Latania scale infested a higher proportion of leaves than fruit